Specialized Positioning of Myonuclei Near Cell-Cell Junctions - Perillo, Margherita; Folker, Eric S. (Frontiers in Physiology, 2018)
Skeletal muscles are large cells with multiple nuclei that are precisely positioned. The importance of the correct nuclear position is highlighted by the correlation between mispositioned nuclei and muscle disease (Gueneau et al., 2009; Spiro et al., 1966). Myonuclei are generally considered to be equivalent and therefore how far nuclei are from their nearest neighbor is the primary measurement of nuclear positioning. However, skeletal muscles have two specialized cell-cell contacts, the neuromuscular (NMJ) and the myotendinous junction (MTJ). Using these cell-cell contacts as reference points, we have determined that there are at least two distinct populations of myonuclei whose position is uniquely regulated. The post-synaptic myonuclei (PSMs) near the NMJ, and the myonuclei near the myotendinous junction myonuclei (MJMs) have different spacing requirements compared to other myonuclei. The correct positioning of pairs of PSMs depends on the specific action of dynein and kinesin. Positions of the PSMs and MJMs relative to the junctions that define them depend on the KASH-domain protein, Klar. We also found that MJMs are positioned close to the MTJ as a consequence of muscle stretching. Our study defines for the first time that nuclei in skeletal muscles are not all equally positioned, and that subsets of distinct myonuclei have specialized rules that dictate their spacing.